2008
DOI: 10.1270/jsbbs.58.331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dose and dose rate of gamma ray irradiation on mutation induction and nuclear DNA content in chrysanthemum

Abstract: We investigated the effect of total irradiation dose and dose rate on flower color mutation and nuclear DNA content as an index of radiation damage in chrysanthemum. Chrysanthemum morifolium cv. 'Taihei' plants grown by in vitro culture were gamma-irradiated with a total dose of 15, 30 and 60 Gy at a rate of 0.5, 1, 2 and 5 Gy/h. Leaf explants cut from the irradiated plants were tissue cultured, and the regeneration rates and frequency of flower color mutation were investigated. Nuclear DNA content was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 12 publications
4
34
0
6
Order By: Relevance
“…The latter group provoked very severe affectations in the material evaluated. These results agree with what was indicated by Yamaguchi et al (2008), who indicated that with low doses of radiation (2-10 Gy), less damage is produced on the genome of the plant.…”
Section: Classification Of the Doses By Cluster Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The latter group provoked very severe affectations in the material evaluated. These results agree with what was indicated by Yamaguchi et al (2008), who indicated that with low doses of radiation (2-10 Gy), less damage is produced on the genome of the plant.…”
Section: Classification Of the Doses By Cluster Analysissupporting
confidence: 92%
“…Este último grupo provocó afectaciones muy severas en el material evaluado. Estos resultados concuerdan con lo indicado por Yamaguchi et al (2008), quienes indican que con bajas dosis de radiación (2-10 Gy) se produce un daño menor en el genoma de la planta. Los resultados expuestos corroboran que la radiosensibilidad en las plantas varía de acuerdo a las dosis de irradiación absorbida, entre otros factores.…”
Section: L a S I F I C A C I ó N D E L A S D O S I S P O R A N á L unclassified
“…Yamaguchi et al (2008) Ionizing radiation can be quantified in terms of absorbed dose (D) which is the amount of ionizing radiation energy deposited per unit mass of irradiated material. Initially, the magnitude was measured in roentgens, called "radiation dose".…”
Section: 30 and 60 Gymentioning
confidence: 99%
“…The gain or loss of a single chromosome can be detected by this method, as shown in Musa (Roux et al 2003), ryegrass (Barker et al 2001), and wheat-rye addition lines (Bashir et al 1993, Pfosser et al 1995. Moreover, Yamaguchi et al (2008) reported that nuclear DNA content of chrysanthemums decreased with increasing dose and dose rate of gamma rays, indicating that the nuclear DNA content could be used as an index of radiation damage.…”
Section: Introductionmentioning
confidence: 98%